Phenylboronic acid-modified polyethyleneimine assisted neutral polysaccharide detection and weight-resolution analysis with a nanopipette. Issue 15 (3rd April 2023) - Xie, Wanyi; He, Shixuan; Fang, Shaoxi; Tian, Rong; Liang, Liyuan; Wang, Deqiang
Abstract : A high-charge polymer molecule PEI-oBA is introduced to assisted low molecular weight neutral dextran detection based on nanopipette technology. Abstract : In this work, an innovative method based on a nanopipette assisted with o -phenylboronic acid-modified polyethyleneimine (PEI-oBA) is proposed to detect neutral polysaccharides with different degrees of polymerization. Herein, dextran is used as the research target. Dextran, with its low molecular weight (10 4 < MW < 10 5 Da), has important applications in medicine and is one of the best plasma substitutes at present. Through the interaction between the boric acid group and a hydroxyl group, the synthesized high-charge polymer molecule PEI-oBA combines with dextran, increasing the electrophoretic force and exclusion volume of the target molecule to obtain a high signal-to-noise ratio for nanopore detection. These results show that the current amplitude increased significantly with the increase of dextran molecular weight. Furthermore, an aggregation-induced emission (AIE) molecule was introduced to adsorb onto PEI-oBA to verify that PEI-oBA combined with a polysaccharide entered the nanopipette together and was driven by electrophoresis. With the introduction of the modifiability of polymer molecules, the proposed method is conducive to improving the nanopore detection sensitivity of other important molecules with low charges and low molecular weights.